Isolation and identification of Pandoraea spp. From bronchoalveolar lavage of cystic fibrosis patients in Iran - Mohammad Tabatabaei; Mahdi Dastbarsar; Mohammad Ashkan Moslehi (BMC, 2019)
Abstract Background Pandoraea species are gram negative, motile, non-spore forming, rod shaped and oxidase positive, obligate aerobes bacteria, and have one polar flagellum. Most of Pandoraea species are associated with lung infections in cystic fibrosis patients. Cystic fibrosis is the most prevalent autosomal recessive hereditary disease in the world that affects various organs of the body. The main important cause of death in these patients is lung involvement. This study was conducted to isolate and identify Pandoraea bacterium from bronchoalveolar lavage and sputum samples of cystic fibrosis patients in Shiraz, Iran. Methods In this research 31 samples of bronchoalveolar lavage and sputum were examined by culture and PCR method. Then confirmed isolates were evaluated for susceptibility to different antibiotics and ability to produce biofilm. Results The results of this study after cultivation, purification and DNA extraction led to the isolation of 4 Pandoraea bacterium by PCR using specific primers. Antibiotic susceptibility test were indicated all isolates were resistant to gentamicin, amikacin and imipenem and susceptible to ciprofloxacin, trimethoprim-sulfumethoxazole, piperacillin and tetracycline. Ability to create biofilm was indicated by some of Pandoraea isolates. According to findings of this study, ability to synthesis biofilm by Pandoraea isolates and resistance to some antibiotics are very important. Conclusions Our study notes the role of P. pnomenusa as an emerging pathogen that can cause chronic lung colonization in CF patients. Identification tools need to be accurate and must be based on molecular techniques. Also our findings should raise awareness about antibiotic resistance in cystic fibrosis patients in Iran and ability of including bacterial agents to produce biofilm is an alarm for public health. Thus clinicians should exercise caution about finding of clinical relevance of this pathogen to the infection and prescribing antibiotics, especially in cases of children infections.